Comprehensive Review of Human Plasmodium falciparum-Specific CD8+ T Cell Epitopes - Heide, Janna; Vaughan, Kerrie C.; Sette, Alessandro; Jacobs, Thomas; Schulze zur Wiesch, Julian (Frontiers in Immunology, 2019)
Control of malaria is an important global health issue and there is still an urgent need for the development of an effective prophylactic vaccine. Multiple studies have provided strong evidence that Plasmodium falciparum-specific MHC class I-restricted CD8+ T cells are important for sterile protection against Plasmodium falciparum infection. Here, we present an interactive epitope map of all P. falciparum-specific CD8+ T cell epitopes published to date, based on a comprehensive data base (IEDB) and literature search. The majority of the described P. falciparum-specific CD8+ T cells were directed against the antigens CSP, TRAP, AMA1 and LSA1. Notably, most of the epitopes were discovered in vaccine trials conducted with malaria-naïve volunteers. Only few immunological studies of P. falciparum-specific CD8+ T cell epitopes detected in patients suffering acutely from malaria or in people from malaria endemic areas have been published. Further detailed immunological mappings of P. falciparum-specific epitopes from a broader range of P. falciparum proteins in different settings and with different disease status are needed to gain a more comprehensive understanding of the role of CD8+ T cell responses for protection, and to better guide vaccine design and to study their efficacy.